PENGARUH JUMLAH BENIH PER LUBANG TERHADAP PERTUMBUHAN DAN HASIL JAGUNG MANIS (Zea mays Saccharata Sturt) - Ahmad - Arwani; Tri - Harwati; Sri - Hardiyatmi (Innofarm:Jurnal Inovasi Pertanian, 2013)
The research on :"The Effect of Number of Seeds Per Hole Against Growth and Yield of Sweet Corn (Zea mays saccharata Sturt)" has been started on October 18, 2012 until January 17, 2013 at the Experimental Garden of the Faculty of Agriculture, University Slamet Riyadi  which is located in the Village Kadipiro, Subdistrict Banjarsari, Town Surakarta. The purpose of this research to determine the effect of the number of seeds per hole on the growth and yield osf the best so that the effectiveness and efficiency of sweet corn planting can be achieved. This research uses the basic design of CRD (completely randomized design) consisting of 3 treatments with 11 replications. The treatment is as follows: A = 1 seed per hole B = 2 seeds per hole C = 3 seeds per hole Data were analyzed using analysis of Variance, which is followed by Duncan's Multiple Range Test (DMRT) at the 5% significant level. The results showed: (1) treatment affected the number of seeds per hole increases the growth and yield of sweet corn crop that is high at the age of 7 weeks after planting, stover fresh weight per plant, fresh weight of stover per hole, stover dry weight per plant, dry weight of stover per hole, heavy cob consumption per plant, cob weight consumption per hole, and the number of cobs per hole. While the number of cobs per plant, number of seed treatment had no effect, (2) treatment 1 seed per plant obtained the highest results on plant height at the age of 7 weeks after planting, stover fresh weight per plant, dry weight of stover per plant, and weight cob consumption per plant, and (3) Treatment of 3 seeds per hole to obtain the highest yield on fresh weight of stover per hole is 2574.55 g, dry weight of stover per hole is 600.81 g, cob weight per hole consumption is 668 g, and the number of cobs hole is 3.55 per ear.   Key words :  Seeds, Growth,Yield , Sweet Corn